Reasonable Accomodation and Freedom of Religion in Quebec - The English Speaking Catholic Council (ESCC) (2007)

Accommodements raisonnables et liberté de religon au Québec - Conseil catholique d’expression anglaise (2007)

Accommodements raisonnables et liberté de religion au Québec - The English Speaking Catholic Council (ESCC) (2007)
We agree with the Commission that “the management of diversity, especially religious diversity... appears above all to pose a problem.” The appearance of a problem seems to have been provoked in large measure by post 9/11 “alarmist media coverage.” Careful reflection will show that there is no problem in reality and that the alarm is not worthy of Quebecers. The ESCC therefore counsels strongly against the temptation to tamper with the current constellation of relevant rights and privileges in Quebec; it is a product of the unique evolution of Quebec society and functions well as “a fair, original model of collective life of which we are proud.”

Reasonable Accommodation and Freedom of Religion in Quebec - The English Speaking Catholic Council (ESCC) (2007)
We agree with the Commission that “the management of diversity, especially religious diversity... appears above all to pose a problem.” The appearance of a problem seems to have been provoked in large measure by post 9/11 “alarmist media coverage.” Careful reflection will show that there is no problem in reality and that the alarm is not worthy of Quebecers. The ESCC therefore counsels strongly against the temptation to tamper with the current constellation of relevant rights and privileges in Quebec; it is a product of the unique evolution of Quebec society and functions well as “a fair, original model of collective life of which we are proud.”

Reasonable Accomodation and Freedom of Religion in Quebec - The English Speaking Catholic Council (ESCC) (2007)

Seniors are an Asset for Quebec - Lincoln, Clifford (2007)

Ethical Guidelines Handbook for the Catholic Laity in Apostolic Service - The English Speaking Catholic Council (ESCC) (2007)

Consultation publique sur les conditions de vie des aînes : Un enjeu de société, une responsabilité qui nous interpelle tous - Conseil catholique d'expression anglaise (2007)
Le Conseil catholique d’expression anglaise aimerait féliciter le gouvernement du Québec pour avoir reconnu l’importance des problèmes affectant les aînés et notre population vieillissante et pour avoir créé le poste de ministre responsable des Aînés. Nous accueillons avec plaisir l’initiative de Mme Marguerite Blais, ministre responsable des Aînés, de tenir des audiences publiques sur les conditions de vie des aînés au Québec. Cet enjeu constitue une grande source de préoccupations pour notre communauté et pour ses institutions au service des personnes âgées, dont l’expérience dans ce domaine est considérable.

Public Consultation on Seniors' Living Conditions : A Social Issue That is the Responsibility of Us All Quebecers - The English Speaking Catholic Council (ESCC) (2007)
The English Speaking Catholic Council would like to congratulate the Government of Quebec for recognizing the importance of issues related to seniors and an aging population and its establishment of the post of Minister Responsible for Seniors. We also welcome the initiative of Mme Marguerite Blais, the Minister Responsible for Seniors, to hold public hearings on seniors’ living conditions in Quebec, an issue on which our community and its institutions serving the elderly have considerable experience and great concern.

The Twenty-Sixth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2007)

Mémoire présenté par le Conseil catholique d’expression anglaise sur les conditions de vie des aînés - The English Speaking Catholic Council (ESCC) (2007)